Continuity between Early Paulicianism and the Seventeenth-Century Bulgarian Paulicians: the Paulician Legend of Rome and the Ritual of the Baptism by Fire - Saldzhiev, Hristo (Studia Ceranea, 2019)
During the Middle Ages two dualistic communities were active in Bulgaria and Bulgarian lands – Bogomils and Paulicians. Paulicians, unlike Bogomils, survived as a separate religious sect up to the 17th century, when most of them gradually accepted Catholicism. The detailed reports of Catholic missionaries, priests and bishops shed light on different aspects of their beliefs and practices from the 17th century. The aim of the present article is to propose an explanation of a strange ritual and a legend spread among the Bulgarian Paulicians and recorded in the above-mentioned reports. The thesis of the article is that the legend and the ritual in question refer to the early history of Paulicianism. The ritual is related to syncretic religious notions and goes beyond the scope of dualism. I try to examine the legend and ritual in the context of Paulician history in the Balkans, especially in the context of Paulician belief system, inherited from the early Anatolian Paulicians.